In vitro evaluation of anti oxidant activity and estimation of total flavonoids in seeds of Psoralea corylifolia plant extracts - Aruna pai; J Madhu Rajendra; JVLN Seshagiri Rao (International Journal of Phytomedicine, 2013)
The present study aims at in-vitro evaluation of anti oxidant activity of n-hexane and ethyl acetate extracts of seeds of Psoralea corylifolia. For evaluating this study 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) method and reducing power method was used.For DPPH method Butylated Hydroxy Anisole (BHA) was used as a positive control and for Reducing power method ascorbic acid was used as a standard reducing agent. All the analysis was made with the use of UV-Visible Spectrophotometer. The content of total flavonoids was measured spectrophotometrically by using the aluminium chloride colorimetric assay where catechin was used as a standard. The extracts showed good DPPH radical scavenging activity and reducing power activity which was found to increase with the increasing concentration of the extracts. The total flavonoid content was found to be 73.09 mg CE/100g. Ethyl acetate extract of Psoralea corylifolia showed more prominent activity when compared to n-hexane extract which could be attributed to the presence of flavonoid content.The study could be further extended to isolate and characterize phytoconstituents from these extracts.